Faktor–Faktor yang Memengaruhi Pendapatan Usahatani Cacing Tanah Mitra CV Rumah Alam Jaya Organik - Santoso, Mikael Adi; Budiraharjo, Kustopo; Handayani, Migie (Universitas Galuh, 2025)
Earthworm farming has quite good prospects. Earthworms have high economic value because they can be sold and generate profits for farmers, however the problem is that marketing is controlled by the company so that the price obtained by earthworm farmers who are partners of CV. Rumah Alam Jaya Organik is the price set according to the agreement. The purpose of this study was to analyze the income of earthworm farming partners of CV. Rumah Alam Jaya Organik and the factors that influence it. This research was conducted in November-December 2024 in Malang and its surroundings. The location was determined purposively with the consideration that Malang is the center of earthworm production in East Java Province because of the supportive climate and geographical conditions and there are companies engaged in the earthworm industry, namely CV. Rumah Alam Jaya Organik. The research method used was a census with 33 farmers as respondents. Data collection techniques were observation and interviews. Data analysis used income analysis, normality test, classical assumption test, and multiple linear regression analysis. The results of the study showed an average income of Rp 8.969.268/month and an average cost of Rp 4.076.453/month, so that the average income of the earthworm farming business of CV. Rumah Alam Jaya Organik partners was Rp 4.892.815/month with an average land area of 1.489 m2. The variables of labor and production volume had a significant effect on income, while the variables of land area, number of seeds, and amount of feed had no effect.